2016
DOI: 10.1097/j.pain.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and pain

Abstract: Sleep and pain are thought to be bidirectional related on a daily basis in adolescents with chronic pain complaints. In addition, sleep problems have been shown to predict the long-term onset of musculoskeletal pain in middle-aged adults. Yet, the long-term effects of sleep problems on pain duration and different types of pain severity in emerging adults (age: 18-25) are unknown. This study investigated the cross-sectional and longitudinal relationship between sleep problems and chronic pain, and musculoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 50 publications
3
33
0
1
Order By: Relevance
“…There is evidence that sleep deprivation affect some fundamental mechanisms of pain and pain inhibition, which conceivably, have a global and not a local effect, such as dysregulation of the endogenous opioid system, increased negative mood in the presence of pain and increased pain catastrophizing [24, 25]. Despite consensus regarding an association between pain and sleep [26], previous studies investigating the association between musculoskeletal pain and sleep have considered musculoskeletal pain without discriminating body sites [27, 28] or have studied the association between sleep and a limited number of painful body sites [29]. A longitudinal study that investigated the ability of insufficient sleep to predict pain in the shoulder, the neck and the low back, concluded that insufficient sleep was a risk factor for NP and LBP but only in girls [29].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that sleep deprivation affect some fundamental mechanisms of pain and pain inhibition, which conceivably, have a global and not a local effect, such as dysregulation of the endogenous opioid system, increased negative mood in the presence of pain and increased pain catastrophizing [24, 25]. Despite consensus regarding an association between pain and sleep [26], previous studies investigating the association between musculoskeletal pain and sleep have considered musculoskeletal pain without discriminating body sites [27, 28] or have studied the association between sleep and a limited number of painful body sites [29]. A longitudinal study that investigated the ability of insufficient sleep to predict pain in the shoulder, the neck and the low back, concluded that insufficient sleep was a risk factor for NP and LBP but only in girls [29].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study showed that participants (~55% women) with sleep complaints had an increased probability (from 14% to 38%) of developing chronic pain 3 years later (Bonvanie et al 2016). Although many researchers support the hypothesis of a bidirectional relationship between sleep and pain, others suggest a unidirectional association, in which alterations in the sleep pattern predict the occurrence of pain (Finan et al 2013).…”
Section: :1mentioning
confidence: 99%
“…Similar relationships have been reported in epidemiological studies. Sleep problems in childhood (age 10-11 years; [ 15 ]) and young adulthood (age 19 years; [ 16 ]) were associated with a higher risk of developing pain problems two to three years later [ 15 , 16 ]. Few studies have empirically examined the mechanisms underlying the sleep-pain relationship in youth; however, negative affect [ 17 ] and depressive symptoms [ 18 ] have been proposed as potential mechanisms underlying the association between sleep impairments and increased pain intensity.…”
Section: Introductionmentioning
confidence: 99%